PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS STEM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF - Mukhlis Mukhlis; Nava Hiqmatunnisaq; Barisah Barisah (Lantanida Journal, 2023)
The purpose of this study is to define the characteristics of STEM-based LKPD, as well as to establish the practicality of STEM-based LKPD and the growth in students' creative thinking abilities. The literature study approach was employed in this study, which was gathered from various sources such as books, journals, and articles linked to the observed research. Determine the topic, obtain information, determine research, collect data sources, prepare data presentation, and compile are the steps in this research. The findings of this research analysis in the three journals studied are visible, specifically the comparison of the development of STEM-based worksheets in improving creative thinking skills to obtain results that are very feasible to develop when compared to the development of critical thinking and scientific literacy. This is demonstrated by the 85.21% improvement in creative thinking skills acquired from STEM-based LKPD development research. Furthermore, based on the analysis of literature studies on the growth of STEM-based LKPD in enhancing creative thinking skills, it has improved year after year, with the feasibility percentage reaching 96% in 2022.